Review of the Influences of Paper Waste Incorporation to Compressive Strength in Concrete - Ismail, Noorli; Hasmy, Syifa Nur Iman (Journal of Structural Monitoring and Built Environment, 2023)
The development of new construction materials is a crucial issue in the building construction industry, as it is one of the most energy and resource-intensive industries. Paper has played a significant role in daily activities since its creation. a wide range of applications thanks to its adaptable qualities. Paper waste can be found in a variety of places, including newspapers, offices and schools. Paper waste is a rich source of fibre and can be utilised as a building material. Utilization of paper wastes can help to reduce pollution and waste in the environment. The purpose of this review study is to highlight and examine some current studies that look into the potential applications of post-consumer paper waste in concrete specimens. The review had been conducted on the research paper between the year 2010 till 2023, paper waste does have potential to be incorporated with cement-based material with the right formulation and percentages. This review data focused on the mechanical properties of concrete.